Measuring the realized niches of animals using stable isotopes: from rats to bears. Issue 2 (27th August 2015) - Hopkins, John B.; Kurle, Carolyn M.
Summary: Stable isotope analysis is a powerful method for estimating the impacts animals have on their environment (resource use), revealing their ecological niches. We demonstrated the use of a stable isotope mixing model for measuring the ecological niches of consumers. In particular, we used the model IsotopeR to estimate the resource use of two species with complex, omnivorous diets: invasive Norway rats from the Aleutian Islands, AK, and American black bears from Yosemite National Park, CA. Marginal posterior distributions for major food sources (for populations, groups and individuals) described the resource axes that partly define the realized niches of these omnivores. We used measures of these resource axes to inform resource management in the Aleutians and Yosemite. Results from our analyses confirm that coastal rats did not rely on marine birds on rat‐infested islands in the Aleutians. Instead, rats foraged primarily on terrestrial plants and preferred amphipods when they were available. We also use stable isotopes to confirm that plants and acorns are the largest contributors to black bear nutrition in Yosemite and learned that female bears foraged for acorns and pine nuts more heavily than males. Although it is unclear if Norway rats can maintain viable populations in the Aleutians without access to marine‐derived animal protein, results from our analyses suggest their dependence on such nutrients. In addition, sex‐specific differences in foraging for high‐fat acorns and pine nuts in Yosemite suggest black bear populations in the Sierra Nevada may be limited by the productivity and health of hard mast species. As demonstrated here, stable isotope analysis has wide applicability for investigating the resource use and ecological niches of animals. We anticipate and encourage its rapid development in this fundamental field of ecology.